Simulation of a stabilised control strategy for PEM fuel cell and supercapacitor hybrid propulsion system for a city bus. (18th October 2018) - Wu, W.; Partridge, J.S.; Bucknall, R.W.G.
Abstract: Fuel Cells (FC) are a clean energy source capable of powering a bus electrically with zero operating emissions. This research investigates the potential of FC and Supercapacitor (SC) hybrid buses for clean city transportation. To investigate the FC/SC hybridisation strategy, a scaled FC/SC hybrid drivetrain has been developed to provide the power system of a scaled bus model. The scaled model was developed as a MATLAB Simulink computer model and cross referenced against the constructed laboratory test rig for validation. A novel control strategy focusing on power balancing between the FC, the SC and the load has been developed and validated in the computer model. It has been demonstrated in both the test rig and computer simulation that the proposed control strategy is capable of maintaining a controlled and stable FC output while meeting different bus load regimes. The validated computer model can provide a reliably representative, convenient and low cost platform for further performance investigation and component optimisation of FC/SC hybrid drivetrains. The control strategy has also been demonstrated to be function as expected after scaling up the developed scaled model to a full scale model which can be used for simulation of practical bus performance. Highlights: Fuel Cell/Supercapacitor hybrid propulsion system simulated and validated with laboratory test bench. Control strategy of keeping FC output constant and controlled in both static and dynamic environment developed. Constant FC output control strategy evaluated and validated with both simulation and laboratory experiment. Power and control system scaled up to enable practical bus analysis.